Don’t Fear Artificial Intelligence, Question the Business Model: How Surveillance Capitalists Use Media to Invade Privacy, Disrupt Moral Autonomy, and Harm Democracy - Jones, Joseph (The Journal of communication inquiry, 2025)
This paper analyzes the causes, consequences, and logic of surveillance capitalism, delineating how behavioral surplus became the latest form of accumulation and questioning its ethical, legal, and material implications. The purpose of this project is to provide a decisively human response to an otherwise reductive, totalizing political economic system that uses equally reductive technology. Using history, political economy, and media ethics, it shows how surveillance capitalists use artificial intelligence (AI) to disrupt the privacy necessary for identity work and distort the moral autonomy necessary for democratic worldmaking. Exploiting human psychology and emotional vulnerabilities, surveillance capitalists interfere with our ability to become better versions of our personal and collective selves. We must therefore reject surveillance capitalism and embrace a more inconclusive understanding of democracy informed by care. While experts and technocrats can endlessly debate the potential outcomes and possibilities, the challenges of AI and an abusive surveillance capitalist system must ultimately be answered by a caring citizenry with equally resilient social institutions.